Investigation of Fluid–Structure Interaction in Stenosed Bifurcated Arteries: Flow Dynamics and Conjugate Heat Transfer - Mudassar Razzaq; Muhammad Adnan Anwar; Kaleem Iqbal; Marcel Gurris (Mathematics)
Atherosclerosis, marked by elevated plaque formation, occurs due to stenosis, which narrows the arterial walls and alters the natural flow path. Previous research has shown that the likelihood of high-rupture stenosis can be linked to temperature distribution variations in bifurcated arteries. In this study, we employ a monolithic Arbitrary Lagrangian–Eulerian (ALE) finite element approach to model heat transfer in fluid–structure interactions within stenosed bifurcated arteries, considering the elasticity of arterial walls. We analyze unsteady, incompressible Newtonian blood flow in a two-dimensional laminar regime, focusing on key factors such as velocity, wall displacement, temperature effects, and the average Nusselt number. Our findings reveal that under pulsatile inflow conditions, minor temperature fluctuations occur under specific waveform flow boundary conditions. Additionally, greater arterial wall flexibility enhances heat transfer between the blood and vessel walls, with flow reflections further contributing to this effect. Lastly, we examine wall shear stress (WSS) at its minimum and maximum values, emphasizing the role of arterial elasticity in influencing these forces.